Electrochemically assisted transport of chlorinated hydrocarbons from aged to clean silt. (20th May 2023) - Fernández-Cascán, J.; Isidro, J.; Guadaño, J.; Sáez, C.; Rodrigo, M.A
Highlights: The rapid depletion of ions during electrokinetic treatment has an impact on the resulting current intensity. Electrokinetic transport of the chlorinated hydrocarbons in aged-polluted silt is limited. Pollutants are not dragged to electrolyte wells during electrokinetic treatment but volatilized. Electroosmotic flow in aged-polluted silt is low and not temperature dependent. Abstract: In this work, the electrokinetic transport of pollutants from polluted to clean soil at two different temperatures is evaluated and validated with a simple phenomenological transport model. For this purpose, real samples highly contaminated with residues from the industrial production of lindane are used. The results show that the dragging of aged pollutant is almost nil (below 0.1% of the initial content), regardless of the experimental conditions tested. During the treatment, the resulting intensity decreases due to ion depletion in the silt. Electro-osmotic fluxes are quite low (0.7 cm d −1 ) and do not depend importantly on temperature. As well, the amounts of pollutants collected in electrolyte wells are negligible. However, there is an important volatilization (from 9 to 12% depending on operation temperature) of the chlorinated organic compounds (COCs) (mainly of lowly chlorinated organics and the gamma and delta isomers of hexachlorocyclohexane) but they are not recovered in the granular activated carbon adsorption but accumulated in the walls and pipes of the mockups. These results are confirmed by volatilization tests in closed bottles dragging the pollutants with an air flow. Additionally, the results accurately fit to a 1-D non-reactive model previously proposed to evaluate the transport of COCs from polluted to clean soil. Effective diffusion coefficients of COCs do not depend on the number of chlorine substitutions. Graphical abstract: Image, graphical abstract − OH, Hydroxyl ions; EO, Electroosmotic Flow; T, Temperature; GAC, Granular Activated Carbon; A, Anode; C, Cathode.